GVHD Pathogenesis, Prevention and Treatment: Lessons From Humanized Mouse Transplant Models - Hess, Nicholas J.; Brown, Matthew E.; Capitini, Christian M. (Frontiers in Immunology, 2021)
Graft-vs-host disease (GVHD) is the most common cause of non-relapse mortality following allogeneic hematopoietic stem cell transplantation (HSCT) despite advances in conditioning regimens, HLA genotyping and immune suppression. While murine studies have yielded important insights into the cellular responses of GVHD, differences between murine and human biology have hindered the translation of novel therapies into the clinic. Recently, the field has expanded the ability to investigate primary human T cell responses through the transplantation of human T cells into immunodeficient mice. These xenogeneic HSCT models benefit from the human T cell receptors, CD4 and CD8 proteins having cross-reactivity to murine MHC in addition to several cytokines and co-stimulatory proteins. This has allowed for the direct assessment of key factors in GVHD pathogenesis to be investigated prior to entering clinical trials. In this review, we will summarize the current state of clinical GVHD research and discuss how xenogeneic HSCT models will aid in advancing the current pipeline of novel GVHD prophylaxis therapies into the clinic.